Rō̜i phlǣ bon dūangčhan - Raphīphan Sāyantrakūn (Mūnnithi Phasān Watthanatham : Mūnnithi Sūn Thanāikhwām Mutsalim, 2012)
Criminal case against children and youth in the three southern border provinces in Thailand with Muslim insurgents and separatist movement; examples of process of the cases involving children and youth according to the enforcement of security laws.